Role of Government and Private Sector on Agribusiness Development: Comparison between the USA and Bangladesh - Md. Mustafizur Rahman; Sreti Rani Sarkar; Kuntala Ghosh; Murshida Khatun; Nuzhat Chowdhury; Tangila Akter; Md Amirul Islam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This comparative research explores the intricate roles of government and the private sector in the growth of agribusiness, analyzing the different approaches used by the USA and Bangladesh. The prevailing paradigm in the USA is market-driven, with an emphasis on private sector dominance, technical innovation, and large-scale agricultural. Bangladesh, on the other hand, takes a hybrid strategy to addressing socioeconomic difficulties, combining government interventions and private efforts with a focus on smallholder empowerment. Divergent tactics, problems, and outcomes in agribusiness growth are revealed by the investigation. Both countries are concerned about concerns such as sustainable practices, market access, and infrastructure. Context-specific solutions, customized to each country's particular socioeconomic context, emerge as critical. The study emphasizes the importance of government and private sector collaboration in fostering resilient and sustainable agribusiness ecosystems, providing useful insights for global agricultural development policy.